2019
DOI: 10.1007/s10764-019-00091-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Local Perceptions of and Attitudes toward Endangered François’ Langurs (Trachypithecus francoisi) in a Human-Modified Habitat

Abstract: Understanding local community attitudes toward wildlife is critical for making context-sensitive conservation planning and management decisions that may facilitate better human-wildlife coexistence. We conducted questionnaire-based interviews with local households in the Qinglong village of Mayanghe National Nature Reserve (MNNR) in China from March to August 2015. We used a mixed analysis technique based on a theoretical framework of categorical variables to explain attitudes to investigate the key factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Understanding local community attitudes toward wildlife is critical for making context-sensitive conservation planning and management decisions that may facilitate better human-wildlife co-existence [87]. In our study area, the attitude of locals toward wildlife species (mostly involved in the conflict) is affected by many factors, e.g., level of education, sighting of wildlife species, crop damage, and livestock owned.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding local community attitudes toward wildlife is critical for making context-sensitive conservation planning and management decisions that may facilitate better human-wildlife co-existence [87]. In our study area, the attitude of locals toward wildlife species (mostly involved in the conflict) is affected by many factors, e.g., level of education, sighting of wildlife species, crop damage, and livestock owned.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reveal that various categories of wildlife utilization have fairly well documented in several Asian countries, encompassing food, pet-keeping, traditional medicine, belief-based practices, trading, and ornamental use [16,17,18]. In Malaysia, the consumption of wildlife as food has a rich history spanning over centuries [19].…”
Section: Categories and Utilization Of Wildlife In Asian Countriesmentioning
confidence: 70%
“…For designing robust protection and management strategies and enabling improved human–wildlife co-existence, it is very important to understand the attitudes of locals towards the wildlife of an area [ 34 ]. The results revealed that in our study area, most locals (96.43%) had negative attitudes towards the wild boar, wishing for its complete elimination from the area.…”
Section: Discussionmentioning
confidence: 99%